Initial clinical evaluation of indigenous 90Y-DOTATATE in sequential duo-PRRT approach (177Lu-DOTATATE and 90Y-DOTATATE) in neuroendocrine tumors with large bulky disease: Observation on tolerability,90Y-DOTATATE post- PRRT imaging characteristics (bremsstrahlung and PETCT) and early adverse effects - Parghane, Rahul; Mitra, Arpit; Bannore, Trupti; Rakshit, Sutapa; Banerjee, Sharmila; Basu, Sandip (World Journal of Nuclear Medicine, 2021)
177Lu-DOTATATE peptide receptor radionuclide therapy (PRRT) alone has lesser potential in the clinical setting of neuroendocrine tumor (NET) with large bulky disease and nonhomogeneous somatostatin receptors (SSTR) distribution, owing to lower energy (Eβmax 0.497 MeV) and a shorter particle penetration range (maximum 2–4 mm) of 177Lu. In large bulky NETs,90Yttrium (90Y) has the theoretical advantages because of a longer beta particle penetration range (a maximum soft tissue penetration of 11 mm). Therefore, a combination of 177Lu and 90Y is a theoretically sound concept that can result in better response in metastatic NET with large-bulky lesion and non-homogeneous SSTR distribution. The aim of the study was to determine the feasibility of combining 90Y-DOTATATE with 177Lu-DOTATATE PRRT as sequential duo-PRRT in metastatic NET with (≥5 cm) including the post 90Y-DOTATATE-PRRT imaging and also to determine early toxicity of the duo-PRRT approach. A total of 9 patients received combination of 177Lu-DOTATATE with 90Y-DOTATATE (indigenously prepared and approved) through sequential duo-PRRT approach. These 9 NET patients were included and analyzed in this study. All 9 patients had undergone post-PRRT 90Y-DOTATATE imaging, including a whole-body planar bremsstrahlung imaging followed by regional single-photon emission computed tomography (SPECT)-computed tomography (CT) imaging and also a regional positron emission tomography–computed tomography imaging. Grading of 90Y-DOTATATE and 177Lu-DOTATATE uptake was done on post-PRRT imaging by both modalities. The size of the lesions ranged from 5.5 cm to 16 cm with average size of 10 cm before sequential duo-PRRT was decided. Sequential duo-PRRT was administered because of stable, unresponsive disease following 177Lu-DOTATATE in 5 patients (55.6%), progressive disease after 177Lu-DOTATATE in 2 patients (22.2%), and with neoadjuvant intent in 2 patients (22.2%). The total cumulative dose of 177Lu-DOTATATE before duo-pRRT ranged from 11.84 GBq to 37 GBq per patient and average administered dose of 27.21 GBq per patient in this study. Out of 9 patients, 8 patients received single cycle of 90Y-DOTATATE (ranging from 2.66 GBq to 3.4 GBq per patient with average administered dose of 3.12 GBq per patient). One patient received two cycles of 90Y-DOTATATE (total dose of 6.2 GBq). Out of 9 patients, 8 patients showed excellent tracer concentration in lesions on post-PRRT 90Y-DOTATATE imaging and the remaining 1 patient showed fairly adequate 90Y-DOTATATE tracer uptake in lesion on visual analysis. There was matched 90Y-DOTATATE uptake with 68Ga-DOTATATE and also with 177LuDOTATATE in all 9 patients. The sequential duo-PRRT was well tolerated by all patients. Two patients (22.2%) developed mild nausea, one patient (11.1%) developed transient mild-grade hemoglobin toxicity, and one patient (11.1%) developed mild-grade gastrointestinal symptoms (loose motion and abdominal pain). No nephrotoxicity, hepatotoxicity, and other hematological toxicity was observed. The combination of the indigenous 90Y-DOTATATE with 177Lu-DOTATATE PRRT in NET as sequential duo-PRRT was well tolerated, feasible and safe in stable, unresponsive/progressive disease following single isotope 177Lu-DOTATATE therapy and also in neoadjuvant PRRT setting with large bulky lesion (≥≥5cm). Post-PRRT 90Y-DOTATATE imaging showed excellent 90Y-DOTATATE uptake in nearly all NET patients. Mild-grade early adverse effects were easily manageable and controllable in this sequential duo-PRRT approach.
Keywords: 177Lu-DOTATATE; 68Ga-DOTATATE PET-CT; 90Y-DOTATATE; duo-PRRT; peptide receptor radionuclide therapy (PRRT); Tandem PRRT